Internalizing students’ social awareness through social studies learning and madrasah culture: A qualitative study at MI Al Fithrah Surabaya (IAIN Kendari, 2026)
Students’ social awareness is central to character formation in Islamic elementary education, yet its internalization through social studies learning remains underexplored. This study analyzed teacher strategies for internalizing students’ social awareness through social studies learning at MI Al Fithrah Surabaya. Using a qualitative descriptive design, data were collected through classroom observation, semi-structured interviews with one teacher and four sixth-grade students, and documentation of learning activities. The findings show that students’ social awareness emerged in four dimensions: cooperation, empathy, responsibility, and honesty, but these values were not consistently enacted in classroom interaction. The teacher internalized social awareness through heterogeneous group discussion, contextual social studies materials, madrasah cultural habituation, and personal-reflective feedback. However, the process was constrained by the absence of an operational affective assessment rubric, digital media influence, student diversity, and limited instructional time. The study contributes to social studies and Islamic elementary pedagogy by showing that madrasah culture can strengthen value internalization when connected with structured classroom practice and formative affective assessment. Keywords: affective assessment; character education; Islamic elementary school; madrasah culture; social awareness; social studies learning